Disaster Risk Reduction: Implementation Module in the Republic of North Macedonia - GJurovski, Marjan; Mocanoski, Mende (University of Applied Sciences Velika Gorica, 2019)
An all-embracing approach is necessary to decrease the vulnerability of our societies through coordinated activities and to lead the way to establishing an effective system for coping with the risks of disasters. The need for an all-embracing approach has been recognized in the Republic of North Macedonia as well, a country where crises have not been a rare phenomenon throughout the years. The area where this country is located doubtlessly makes it a geographical, economic and geopolitical unique centre. In such circumstances, complemented with the great progress of technological-technical development, the Republic of North Macedonia has decided to join the countries which have agreed to a common approach in the realization of common interest – disaster risk reduction. Disaster risk reduction is a concept, which has been defined by UNISDR. It aims at reducing the consequences caused by natural accidents (earthquakes, floods, etc.) by applying the method of preventive action. The all-embracing approach is applied for the identification of the risk factors which cause crises and systematic efforts are made for their neutralization. Hence, the Government of the Republic of North Macedonia officialised the National Platform for Disaster Risk Reduction in 2009. A number of subjects act on its basis – participants that are united for a common national and international interest – disaster risk reduction. The idea is to establish a mechanism which will enable effective coordination of intellectual knowledge and accessible resources through a systematic approach, as well as securitization of disaster risks and their integration in the political-security agenda on a national level.
Keywords: National Platform, Risks, Floods, Crisis Management, Protection and Rescue.